Efficacy of Dulaglutide in a Patient With Type 2 Diabetes, High Cardiovascular Risk, and HIV: A Case Report - Dardano, Angela; Aragona, Michele; Daniele, Giuseppe; Miccoli, Roberto; Del Prato, Stefano (Frontiers in Endocrinology, 2022)
Background Type 2 diabetes (T2D) is a common comorbidity in people living with HIV (PLWH). Anti-hyperglycemic treatment in PLWH is still a challenge, and no randomized controlled studies using new glucose-lowering agents are currently available. Case Description A 55-year-old-women was admitted to our Diabetes Unit because of hyperosmolar hyperglycemic state (HHS) and sepsis. The medical history included HIV infection and insulin-treated diabetes. On clinical examination, the lady appeared dehydrated with dry buccal mucosa, tachycardia, altered mental status, genital infection, and fever. On admission, plasma glucose was 54.5 mmol/L, HbA1c 155 mmol/mol, osmolarity 389.4 mOsm/kg, bicarbonate 24.6 mmol/L with no detectable serum ketones. The patient was treated with i.v. fluid and insulin, and antibiotic therapy commenced. Upon HHS and sepsis resolution, a basal-bolus insulin therapy was implemented that was followed by significant improvement of daily glucose profiles and progressive reduction of insulin requirement until complete discontinuation. A low dose of metformin plus linagliptin was started. Since a severe atherosclerotic disease was diagnosed, a GLP-1 receptor agonist, dulaglutide, was added to metformin upon linagliptin withdrawal with maintenance of good glycemic control, treatment adherence and amelioration of quality of life and no side effects. Conclusion This case suggests that GLP-1 receptor agonist therapy may be effective and safe for treatment of T2D with high cardiovascular risk in PLWH, supporting the need of clinical trials directly assessing the safety and the efficacy of GLP-1 receptor agonist in these individuals.